The Potency of Kitolod (Isotoma longiflora (L)Presl.) Herb Extract as a Cure for Cervical Cancer: an in Vitro Study of Hela Cells - Hapsari, Atikah; Asti, Dhinar; Selviana, S; Hidayati, Ria; Kumalla, Novea; Suhendi, Andi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2016)
Cervical cancer is the leading cause of death in women in the world. Cases of cervical cancer are the majority causes of death occurring in developing countries. The existing medicines which have a lot of functions as anticancer, however, still can damage the normal cells in our body. Cancer treatment using chemotherapy also has some side effects. The condition encourages researchers to explore anticancer cure made of natural ingredient. This research was conducted to find the potency of ethanol extract of herb kitolod (Isotoma longiflora (L) Presl.) as a cervical cancer cure to heLa cell. The method being used for the cytotoxic test on HeLa cells was MTT assay. Absorbant performed by ELISA reader at a wavelength of 595nm. Phytochemical screening which had been conducted showed a significant result that kitolod plants contain secondary metabolites compounds such as flavonoids, steroids, saponins, tannins and alkaloids. The results of cytotoxic test of the kitolod herb ethanol extract on HeLa cells by using MTT assay method acquired a value of IC50 of 227 μg/mL. This study showed that the ethanol extract of the herb kitolod had the potency to inhibit cervical cancer cells (HeLa cells) in a moderate ability.